Depiction of Vyala and Mithuna figures on the recesses - Temples of India Project Team (Jio Institute, 2024)
This is the north-facing elevation of the central shrine in the Neelkanth Mahadev Temple. The central bhadra (central projection) has a depiction of Narasimha killing the demon Hiranyakashipu. The recesses have vyala (composite mythical creatures) and mithuna/maithuna (amorous couples) figures.